PERLINDUNGAN TERHADAP CORAK INSANG SEBAGAI WARISAN BUDAYA TRADISIONAL - NIM. A1011191317, TURSANDI ARIYANDA RAMADAN (Jurnal Fatwa Hukum, 2025)
Abstract  Insang Pattern Woven Cloth in Pontianak City is a source of copyright assets, where each creation has a moral and economic asset so that efforts to protect the creation are needed from craftsmen and local governments. Insang Pattern Woven Cloth has not been registered at all, because craftsmen are less aware of the importance of registering the Insang Pattern Woven Cloth that has developed, this negligence of course has the potential to cause problems such as fabric plagiarism.This study uses a normative legal research type and is descriptive analysis. The data sources used are primary data and secondary data consisting of primary legal materials and secondary legal materials. The data collection techniques used are observation techniques, interview techniques, and documentation study techniques. Then the data analysis uses qualitative methods.The results of the study show that the Pontianak City Government has recorded the Insang Pattern as a protected work under communal intellectual property and cultural advancement, which provides protection for its creators from protection through inventory, security, maintenance, and storage and the Insang Pattern has also been recorded as communal wealth, which refers to a form of appreciation for traditional culture that is collectively owned by the community, not individuals and the Pontianak City Government has made various efforts to preserve the Insang Pattern, this includes research, data collection, and proposing the Insang Pattern as an intangible cultural heritage at the national level. In addition, the cultural festival held in Pontianak City and the publication of the mayor's regulation requiring the use of Insang Pattern by ASN on certain days show the government's commitment to cultural preservation.Keywords: Communal Intellectual Property, Traditional Cultural Expressions and Gill Pattern Woven Fabrics.  Abstrak  Kain Tenun Corak Insang di Kota Pontianak merupakan sumber aset kekayaan hak cipta, yang mana setiap ciptaan memiliki sebuat aset yang moral dan ekonomi sehingga diperlukan upaya perlindungan terhadap ciptaan tersebut dari pengrajin maupun pemerintah daerah. Kain Tenun Corak Insang masih belum sama sekali didaftarkan, karena pengrajin kurang menyadari betapa pentingnya mendaftarkan Kain Tenun Corak Insang yang sudah berkembang, kelalaian tersebut tentu saja berpontensi menimbulkan permasalahan seperti plagiatrisme kain.Penelitian ini menggunakan jenis penelitian yuridis normatif dan bersifat deskriptif analisis. Sumber data yang digunakan yaitu data primer dan data sekunder yang terdiri dari bahan hukum primer, dan bahan hukum sekunder. Teknik pengumpulan data yang dilakukan yaitu teknik observasi (pengamatan), teknik wawancara (interview), dan teknik studi dokumentasi. Kemudian analisis data menggunakan metode kualitatif.Hasil penelitian menunjukkan bahwa pemerintah Daerah Kota Pontianak telah mencatat Corak Insang sebagai karya yang dilindungi di bawah kekayaan intelektual komunal dan pemajuan kebudayaan, yang memberikan perlindungan melalui inventarisasi, pengamanan, pemeliharaan, dan penyelamatan dan Corak Insang juga telah dicatat sebagai kekayaan komunal, yang mengacu pada bentuk apresiasi terhadap budaya tradisional yang dimiliki secara kolektif oleh masyarakat, bukan perorangan dan Pemerintah Daerah Kota Pontianak telah melakukan berbagai upaya untuk melestarikan Corak Insang, ini termasuk penelitian, pendataan, dan pengusulan Corak Insang sebagai warisan budaya tak benda di tingkat nasional. Selain itu, festival budaya yang digelar di Kota Pontianak dan penerbitan peraturan walikota yang mewajibkan penggunaan Corak Insang oleh ASN pada hari-hari tertentu menunjukkan komitmen pemerintah dalam pelestarian budaya.Kata Kunci: Kekayaan Intelektual Komunal, Ekpresi Budaya Tradisional dan Kain Tenun Corak Insang.